2018
DOI: 10.1002/adem.201800271
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solid Solute and Precipitate Phase on Young's Modulus of Binary Mg–RE Alloys

Abstract: The Young's modulus for a series of binary Mg–Gd and Mg–Nd alloys are studied in the present work. Fine and homogeneous grain structures are prepared by using hot extrusion. The results demonstrate that the Young's modulus of Mg–Gd alloys increase linearly by the increase of Gd in solid solution. Aging treatments are applied to the Mg–0.79–2.43 at% Gd alloys. A needle‐like orthorhombic structure β′ phase is formed in Mg matrix. Due to a higher Young's modulus of the intermetallic β′ phase which is estimated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Mg also plays an important role in the synthesis of proteins and nucleic acid, the integrity of mitochondria and enzymes, the stabilization of biological membranes, and the modulation of transport functions [ 12 , 18 , 19 ]. The elastic modulus of Mg is ~45 GPa [ 20 , 21 , 22 , 23 ], which is close to the value of cancellous bone (10–30 GPa). Mg is also lightweight and exhibits a high strength-to-weight ratio.…”
Section: Introductionmentioning
confidence: 56%
“…Mg also plays an important role in the synthesis of proteins and nucleic acid, the integrity of mitochondria and enzymes, the stabilization of biological membranes, and the modulation of transport functions [ 12 , 18 , 19 ]. The elastic modulus of Mg is ~45 GPa [ 20 , 21 , 22 , 23 ], which is close to the value of cancellous bone (10–30 GPa). Mg is also lightweight and exhibits a high strength-to-weight ratio.…”
Section: Introductionmentioning
confidence: 56%
“…The measured Young's modulus during heating and cooling test cycles fit well with each other. The room temperature Young's modulus of the alloy is 43.7 GPa, and it is in the normal range of 40-50 GPa ambient Young's modulus that is generally expected for cast Mg alloys [40,41] With the increase of temperature from room temperature to the elevated temperature of 300 °C, the thermal conductivity of the alloy increases to 124 W/m•K.…”
Section: Ambient and Elevated Modulusmentioning
confidence: 85%
“…After T4 treatment, only the equilibrium second phase Mg 41 Nd 5 was identified. Notably, our previous work [39] demonstrated that in the as-extruded Mg-5Nd alloy the second phase is Mg 41 Nd 5 rather than Mg 12 Nd. Before the present Mg-5Nd alloy was extruded at high temperature 450°C, a homogenization treatment was performed at 440°C.…”
Section: A Microstructurementioning
confidence: 96%
“…Our previous work indicated that after hot extrusion the stable Mg 41 Nd 5 phase exists in Mg-5Nd alloy. [39] The reason for choosing such a content of 5 wt pct Nd, which is slightly higher than the limit of solid solubility at Mg-Nd eutectic temperature, is to retain a part of undissolved stable Mg 41 Nd 5 phase after solid solution treatment. In addition, it offers chances to modify both the phase types and distributions of intermetallics using heat treatments.…”
Section: Introductionmentioning
confidence: 99%